Analisis Fenomena Bullwhip Effect pada Sistem Rantai Pasok Kerupuk Nanas (UMKM Dapoer Bu Aas, Subang) - Hanik Atus Sangadah; Ferdi Fathurohman; Hanifah Sakha; Asriyani Asriyani (Universitas Teuku Umar, 2026)
Bullwhip Effect is a phenomenon often found in supply chain management which describes a mismatch between consumer demand and the amount of production of business actors. The mismatch can lead to inventory imbalances, wasted resources, and reduced operational efficiency. The purpose of this study is to analyze the Bullwhip Effect value, identify its main causes, and formulate improvement strategies to increase supply chain efficiency for pineapple cracker products from the Dapoer Bu Aas MSME. The methods use a Bullwhip Effect analysis, fishbone diagram, and SWOT analysis with production, demand, and distribution data throughout 2024. The results show a Bullwhip Effect value of (1.0). This figure indicates that the mismatch between production and demand is relatively small, but there are significant fluctuations in February, September and October. The main causes include production not meeting demand, and the absence of a forecasting system. Recommendations for improvement strategies that can be implemented by MSMEs include improving management systems, implementing forecasting methods, digitalizing bookkeeping, and strengthening the supply chain through diversifying raw material sources and expanding distribution channels.